Additive manufacturing with functionalized nanomaterials - Singh, Sunpreet, 1989-; Hussain, Chaudhery Mustansar (Elsevier, 2021)
The greatest benefits of nanoscale additive manufacturing lie in biomedicine, smart devices/sensors, energy harvesting, aerospace, and manufacturing. This book explores the recent applications of functionalized nanomaterials-based additive manufacturing to benefit different manufacturing domains, including design and process aspects, as well as outlining major application areas. This book summarizes recent progress of functionalized nanomaterials-based additive manufacturing on both an experimental and a theoretical model level. Though nanomaterials can be fabricated by bottom-up and top-down approaches (techniques include lithography, photolithography, and micro-machining), the applications of additive manufacturing processes are increasing at an exponential rate and therefore, the demand for high-performance materials has been greatly increasing. Recent applications covered in this book include biomedicine, aerospace, automobile, waste recycling, and energy storage devices. Environmental, regulatory and safety issues are also discussed. This book is an important reference source for materials scientists and engineers who are seeking to improve their understanding of how functionalized nanomaterials are playing an increasingly important role in the additive manufacturing process.
Includes index.
Keywords: Additive manufacturing.; Nanostructured materials.; elektronické knihy; electronic books